Pengaruh Organizational Citizenship Behaviour terhadap Kinerja Karyawan di Balai Besar Pelatihan Vokasi dan Produktivitas (BBPVP) Kota Bandung - Rd Khofifah Shahnaz; Indra Fajar Alamsyah (Bandung Conference Series: Business and Management, 2023)
Abstract. Organizational Citizenship Behaviour is a performance that is expected to increase mutual understanding and tolerance between employees and has a role in the effectiveness of employee performance appraisal, especially in the development of an organization. The more detailed an employee performance appraisal, the more related the issue of Organizational Citizenship Behaviour as an alternative to employee performance appraisal with an informal assessment system so that employees feel involved in organizational decisions. The population that object of this research is the Bandung City Job Training and Productivity Center (BBPVP), which is a public sector government training institution. Research data is obtained from questionnaires that have been distributed with data collection techniques carried out in the form of several questions or statements via g-form to several respondents to be answered. Based on the results of descriptive analysis, it can be seen that the Organizational Citizenship Behaviour variable is included in the very good category, and the Employee Performance variable is included in the very good category. In addition, based on the results of the study it is known that Organizational Citizenship Behaviour has a positive and significant effect on Employee Performance of 0.715 or 71.5% while the rest is influenced by other variables not examined in this study. As for practical advice to agencies on Organizational Citizenship Behaviour variables, it is hoped that the application of these attitudes will become a systematic culture or habit to increase familiarity and solidarity such as glamping, social gathering, and other activities that can be done together. As well as for the Employee Performance variable, superiors must have tiered performance supervision and ensure that each employee can pass at each level. Then theoretical suggestions for future researchers are advised to take different independent variables, for example leadership and so on and different methods such as using multiple linear regression methods. Abstrak. Organizational Citizenship Behaviour merupakan suatu kinerja yang diharapkan dapat meningkatkan rasa saling pengertian dan toleransi antar karyawan dan memiliki peran dalam efektivitas penilaian kinerja karyawan, terutama dalam pengembangan suatu organisasi. Semakin terperinci suatu penilaian kinerja karyawan, maka semakin terkait pula isu Organizational Citizenship Behaviour sebagai salah satu alternatif penilaian kinerja karyawan dengan sistem penilaian yang bersifat informal sehingga karyawan merasa terlibat dalam keputusan organisasi. Populasi yang menjadi objek penelitian ini adalah Balai Besar Pelatihan Vokasi dan Produktivitas (BBPVP) Kota Bandung yang merupakan sektor publik sebuah lembaga pelatihan Pemerintah. Data penelitian diperoleh dari kuesioner yang telah disebarkan dengan teknik pengumpulan data yang dilaksanakan dalam bentuk beberapa pertanyaan atau pernyataan melalui g-form kepada beberapa responden untuk dijawab. Berdasarkan hasil analisis deskriptif dapat diketahui bahwa variabel Organizational Citizenship Behaviour termasuk dalam kategori sangat baik dan variabel Kinerja Karyawan termasuk dalam kategori sangat baik. Selain itu, berdasarkan hasil penelitian diketahui bahwa Organizational Citizenship Behaviour berpengaruh positif dan signifikan terhadap Kinerja Karyawan sebesar 0,715 atau 71,5% sedangkan sisanya dipengaruhi oleh variabel lain yang tidak diteliti dalam penelitian ini. Adapun saran praktis kepada instansi pada variabel Organizational Citizenship Behaviour yaitu dengan diharapkan nya penerapan sikap tersebut menjadi budaya atau kebiasaan yang ter sistem untuk meningkatkan keakraban dan solidaritas seperti glamping, arisan, dan kegiatan lainnya yang dapat dilakukan bersama. Serta untuk variabel Kinerja Karyawan, atasan harus mempunyai pengawasan kinerja yang berjenjang dan memastikan setiap karyawan dapat lolos di setiap tingkatan nya. Lalu saran teoritis bagi peneliti selanjutnya disarankan untuk mengambil variabel bebas yang berbeda, misalnya kepemimpinan dan lain sebagainya serta metode yang berbeda seperti menggunakan metode regresi linier berganda.